Perancangan Promosi Video Marketing pada PT. Midi Utama Indonesia Branch Medan - Lutfi, Muhammad; Nasution, Muhammad Irwan Padli (Ikatan Da'i Indonesia, 2023)
In an era that continues to develop in the digital world, marketing has become an important component in achieving global business success. With technological developments and changes in consumer behavior, marketing strategies continue to experience innovation. One of the biggest innovations in recent years is the use of promotions through video marketing. Promotion through video marketing has become an integral part of companies' efforts to increase their brand awareness, interact with a wider audience, and achieve success in an increasingly competitive business environment. In the midst of increasingly fierce competition, PT. Midi Utama Indonesia Medan Branch, a company operating in the field of (company business specifications), made major changes in its marketing strategy by utilizing promotions through video marketing. This research uses a qualitative method with a descriptive approach. So in this research the researcher will conduct an in-depth review of the planning and implementation of video marketing promotion strategies that have been implemented by PT. Midi Utama Indonesia Medan Branch. Researchers will also explore the main steps in the planning, production and promotion process of marketing videos.